Bridge Assessment and Health Monitoring with Distributed Long-Gauge FBG Sensors - Chunfeng Wan; Wan Hong; Jianxun Liu; Zhishen Wu; Zhaodong Xu; Shu Li (International Journal of Distributed Sensor Networks)
Most sensors for structural testing and health monitoring are “point” sensors which strongly limit the ability to correct damage detection and structural assessment. In this paper, long-gauge FBG sensor which can sense the whole area within the gauge length is introduced. Bridge assessment and health monitoring with the microstrain distribution acquired by the distributed long-gauge FBG sensor are also studied. Experiments were conducted and application to a real prestressed box bridge was also implemented. Static and dynamic testing results show that distributed long-gage FBG sensing technique can obtain not only the global information such as bridge deflection and natural frequency, but also the local parameters such as strain and modal macrostrain to detect damage of the bridge. It shows that structural assessment and health monitoring based on the proposed technique have great potential in maintenance of civil engineering infrastructures.